Remote monitoring of periodic limb movement disorder during sleep - Nikishov, Artem; Kletsov, Andrey; Kayumova, Dinara; Han, Jonghee; Sim, Heonkyo; Shin, Hongbeom (IEEE Global Communications Conference (Online), 2024)
Personal sleep control monitoring nowadays is gaining popularity both thanks to rapid development of compact and cheap sensors and to increase of understanding of human movements behavior during sleep. One relevant direction is monitoring of periodic limb movement disorder (PLMD). PLMD is a sleep disorder, which is characterized by repetitive jerking, cramping, or twitching of lower limbs during sleep, and can be symptom of diabetes, iron deficiency, uremia, anemia, etc. With appearance of compact and accurate ultra wideband radars, PLMD monitoring became available for users at home environment. In this paper, we propose an algorithm of PLMD monitoring during sleep using off-the-shelf UWB radar. The applicability and accuracy of the method was verified at clinical tests with 110 subjects. Proposed algorithm achieves 0.86 F1-score.